2021
DOI: 10.3389/fimmu.2021.652294
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin Plays an Important Role in Regulating the Growth and Health Status of Juvenile Blunt Snout Bream (Megalobrama amblycephala), as Evidenced by Pathological Examination

Abstract: The present study aimed to assess the role of tributyrin (TB) in regulating the growth and health status of juvenile blunt snout bream (Megalobrama amblycephala) through an 8-week feeding experiment. Six groups were fed experimental diets with added TB percentages of 0% (control group), 0.03%, 0.06%, 0.09%, 0.12% and 0.15%. The present results showed that TB supplementation in feed had some positive impacts on FW, WG, FCR and SGR, and the best results were found in the 0.06% TB group (P<0.05). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…In addition, the results of the present study indicated that the addition of 500-1500 mg/kg TB to the high CRM diet significantly improved the antioxidant enzyme activity in the serum, with an optimal concentration of 1000 mg/kg. Similar studies have confirmed that TB can significantly increase the serum content of SOD, GPx and CAT and significantly reduce the content of MDA under oxidative stress in blunt snout bream (Liang et al, 2021). A possible mechanism is that TB can increase the content of ATP (Li, Hou, et al, 2015;Li, Feng, et al, 2015), which plays an important role in activating PI3K/Akt signalling (Chen et al, 2014), further activating the Nrf2 signalling pathway and subsequently promoting the transcription of antioxidant enzymes and improving its gene expression, which improves the activity of antioxidant enzymes (Wu et al, 2018).…”
Section: Ta B L Esupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, the results of the present study indicated that the addition of 500-1500 mg/kg TB to the high CRM diet significantly improved the antioxidant enzyme activity in the serum, with an optimal concentration of 1000 mg/kg. Similar studies have confirmed that TB can significantly increase the serum content of SOD, GPx and CAT and significantly reduce the content of MDA under oxidative stress in blunt snout bream (Liang et al, 2021). A possible mechanism is that TB can increase the content of ATP (Li, Hou, et al, 2015;Li, Feng, et al, 2015), which plays an important role in activating PI3K/Akt signalling (Chen et al, 2014), further activating the Nrf2 signalling pathway and subsequently promoting the transcription of antioxidant enzymes and improving its gene expression, which improves the activity of antioxidant enzymes (Wu et al, 2018).…”
Section: Ta B L Esupporting
confidence: 66%
“…Tributyrin (TB), a precursor of butyric acid, can pass through the stomach without changing the biological characteristics of butyric acid and cannot be digested by digestive enzymes (Chen & Breitman, 1994;Su et al, 2004). Studies have reported that the addition of TB into high soybean meal diets can improve the growth performance, immunity and intestinal health of common carp (Cyprinus carpio L.; Xie et al, 2021), yellow drum (Nibea albiflora; Zhu et al, 2020), blunt snout bream (Megalobrama amblycephala; Liang et al, 2021) and black sea bream (Acanthopagrus schlegelii; Volatiana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…were also observed in blunt snout bream, where the expression of intestinal TGFβ was significantly increased by dietary 0.03% tributyrin (Liang et al, 2021). Currently, there is no report on the association of tributyrin with hepcidin in aquatic animals, while sodium butyrate enhanced distal intestinal immune function in grass carp was closely associated with the upregulation of hepcidin expression (Tian et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported that an appropriate dietary TB level significantly increased the growth of some teleost fish. 0.1g/kg dietary TB supplementation produced the greatest value of growth performance in tawny puffer (Zhai et al, 2014); optimum tributyrin supplementation for juvenile black sea bream is 2.24 g/kg in the 45% soya bean meal diet (Volatiana et al, 2020); dietary 1.0 g/kg tributyrin supplementation in high-soya bean meal diet has significantly improved growth performance of yellow drum (Tan et al, 2020); 2.0 g/kg-4.0 g/kg dietary TB supplementation led to high growth performance in common carp fed all-plant diets (Xie et al, 2020); 0.3-0.6 g/kg TB supplementation in diet significantly increased the growth of blunt snout bream fed with high-plant diets (Liang et al, 2021). In the present study, it is also found that dietary TB supplementation improved the growth of turbot.…”
Section: D a Bmentioning
confidence: 99%
“…In intestinal tract TB is decomposed by pancreatic lipase to release butyric acid, which better exerts the function of butyric acid in the intestine (Li et al, 2009). It was reported recently in aquatic animal that the diet supplemented with TB could promote the intestinal healthy development, enhance the immune function and improve the growth performance of tawny puffer (Takifugu flavindus) (Zhai et al, 2014), black sea bream (Acanthopagrus schlegelii) (Volatiana et al, 2020), yellow drum (Nibea albiflora)(Tan et al, 2020) , common carp (Cyprinus carpio) (Xie et al, 2020) and blunt snout bream (Megalobrama amblycephala) (Liang et al, 2021). However, the research on TB in the culture of turbot has not been reported yet.…”
mentioning
confidence: 99%